Experimental Investigation of Water–Sand Mixed Fluid Initiation and Migration in Porous Skeleton during Water and Sand Inrush - Xin Yang; Yong J. Liu; Ming Xue; Tian H. Yang; Bin Yang (Geofluids)
Water–sand inrush is one of the most serious disasters for mining in China. The evaluation of the occurrence and development of a high-concentration water and sand mixed fluid is an important issue for mining in China. In this study, contraposing to the 3 phases of water–sand inrush, three kinds of experiments are designed for the investigation of initiation, development, and occurrence of the disaster. A new sand–water transport testing system is setup to perform the tests. The results show that there are two key points in the disaster: (1) sand particle incipient motion and (2) porous skeleton structural instability. The incipient motion of sand grains is accompanied with the phenomena of volumetric dilatation and granular fluidization. The critical velocity of the incipient motion of the water–sand mixed fluid is significantly affected by the particle size and external stress. The interaction between water and sand grains is the key factor affecting the motion characteristics of water–sand mixture. When the hydraulic conditions exceed the threshold, the water and sand grains are mutually promoted, and the aquifer skeleton becomes unstable. Furthermore, during the water–sand inrush, the curves of volumetric flow rates of sand and water, respectively, for different samples manifest as two distinct waveforms.